The drop out - Heiss, Silke (Department of English Language and Literature, 2014)
The Drop Out is a Bildungsroman in three parts. The reader follows a young European woman's quest for self-discovery. Manja Levsky's journey commences amid the South African white Left during the late 1980s. Manja has two aims: to discover what it means to be a woman; and to create personal independence from the status quo.